2018
DOI: 10.1002/cnma.201800064
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Hybrid Perovskite Solar Cells Modified with Polyethylenimine via Ionic Bonding

Abstract: Organic-inorganic hybrid perovskites are highly promising materials for photovoltaic applications, yet their rapid degradation remains a significant challenge. Here, three highly stable methylammonium lead iodide (MAPbI 3 ) perovskite films modified with polyethylenimines (PEIs) of different molecular weights (Mw = 600, Mw = 10000 and Mw = 70000) were successfully obtained. The PEIs were used as an additive in the perovskite to determine their influences on the structure, film quality, and performance of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Take PEIE as an example, the abundant amino and imine groups in PEIE tend to be protonated and make the terminal domains positively charged, which can bond with halide ions of perovskite and strengthen the film uniformity and compactness. [245] Under bottom-contact conditions, the implementation of SAMs can also modify the perovskite growth at the contact region, which is similar to the observation in OSC-based electronics. [246][247] Generally, the crystallinity of the resulting thin film highly depends on the affinity of SAM's terminal group to the perovskite.…”
Section: Passivation Effectsupporting
confidence: 64%
“…Take PEIE as an example, the abundant amino and imine groups in PEIE tend to be protonated and make the terminal domains positively charged, which can bond with halide ions of perovskite and strengthen the film uniformity and compactness. [245] Under bottom-contact conditions, the implementation of SAMs can also modify the perovskite growth at the contact region, which is similar to the observation in OSC-based electronics. [246][247] Generally, the crystallinity of the resulting thin film highly depends on the affinity of SAM's terminal group to the perovskite.…”
Section: Passivation Effectsupporting
confidence: 64%
“…For example, butylphosphonic acid 4-ammonium chloride with a combination of phosphate and amino functional groups can simultaneously passivate MA + , Pb 2+ , and I – defects . Additionally, suaraine, polyaniline, and quaternary ammonium salts have been shown to be good capping ligands for MAPbI 3 bulk, MAPbI 3 film, and MAPbBr 3 bulk, respectively. , Peptides containing both −NH 3 + – and −COO – – in one molecule have been used to passivate MA + , Pb 2+ , and Br – of MAPbBr 3 perovskite NCs . Similarly, trifunctional l -cysteine has been used to passivate MAPbBr 3 perovskite NCs and induced self-assembly of perovskite NCs, based on synergistic effects among −NH 3 + –, −COO – –, and −SH– groups .…”
Section: Surface Chemistry Of Colloidal Halide Perovskite Ncsmentioning
confidence: 99%
“…Indeed, it has been previously demonstrated that PEIE can effectively modify the surface of perovskites by forming strong hydrogen bonding interactions with surface defects. 47 Fig. 3e and f present the hole and electron transfer characteristics of the DPP-modified and PEIE surface treated perovskite FET where complete elimination of hysteresis is observed.…”
Section: Improvements In Mobility and Elimination Of Hysteresismentioning
confidence: 99%